Behavior-based management of ecosystems - Provenza F.D.; Papachristou T.G. (Nutritional and foraging ecology of sheep and goats, 2009)
Once understood, behavioral principles and processes can be translated into practices that provide an array of solutions to the challenges people face in managing to maintain livelihoods and the integrity of landscapes. Unlike the infrastructure of a ranch such as corrals, fences, and water development, behavioral solutions cost little to implement and they are not fossil-fuel intensive. They are also easily transferred from one situation to the next. Unfortunately, scientists and managers often ignore the power of behavior to transform systems, despite compelling evidence. The environment, continually interacting with the genome during the growth and development of an organism, creates behavioral responses that in social animals are transferred across generations. Given time, that forms the basis for what it means to be locally adapted to a landscape. Though experiences during development in utero and early in life are especially critical, genome-environment interactions continue throughout life. Thus, the issue is not whether if soils, plants, herbivores, and people are adapting to ongoing changes in biophysical and social environments; they all do so continually. For those willing to understand how these ongoing interactions influence behavior, the potential is unlimited. In the case of grazing, behavioral solutions are increasingly attractive given growing social, economic and ecological concerns with wildfires, herbicides, and mechanical means of rejuvenating landscapes. Behavior-based management offers opportunities, for example, to use understanding of: (i) the relationship between palatability and plant biochemistry to rejuvenate landscapes to benefit wild and domestic animals; (ii) the importance of variety in the diet and daily grazing sequences of livestock to enhance wildlife benefits to land owners, managers, and users; and (iii) the value of biochemical complementarities for developing plant mixes for pastures that provide a full range of benefits - nutrition and health for plants, herbivores, and people - without the unsustainable fossil fuel costs associated with fertilizers, herbicides, insecticides, antibiotics and anthelmintics.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)